A dose perturbation tool for robotic radiosurgery: Experimental validation and application to liver lesions. Issue 11 (12th September 2022) - Liu, Ming; Cygler, Joanna E.; Dennis, Kristopher; Vandervoort, Eric
Abstract: Background: An analytical tool is empirically validated and used to assess the delivered dose to liver lesions accounting for different types of errors in robotic radiosurgery treatment. Material and methods: A tool is proposed to estimate the target doses taking into account the translation, rotation, and deformation of a target. Translational errors are modeled as a spatial convolution of the planned dose with a probability distribution function derived from treatment data. Rotations are modeled by rotating the target volume about the imaging isocenter. Target deformation is simulated as an isotropic target expansion or contraction based on changes in inter‐fiducial spacing. The estimated dose is validated using radiochromic film measurements in nine experimental conditions, including in‐phase and out‐of‐phase internal‐and‐external breathing motion patterns, with and without uncorrectable rotations, and for homogenous and heterogeneous phantoms. The measured dose is compared to the perturbed and planned doses using gamma analyses. This proposed tool is applied to assess the dose coverage for liver treatments using D99/Rx where D99 and Rx are the minimum target and prescription doses, respectively. These metrics are used to evaluate plan robustness to different magnitudes of rotational errors. Case studies are presented to illustrate how to improve plan robustness against delivery errors. Results: In the experimental validations, measured dose agrees with the estimated dose at the 2%/2 mm level. When accounting for translational and rotational tracking residual errors using this tool, approximately one‐fifth of targets are considered underdosed (D99/Rx < 1.0). If target expansion or contraction is modeled, approximately one‐third of targets are underdosed. The dose coverage can be improved if treatments are planned following proposed guidelines. Conclusion: The dose perturbation model can be used to assess dose delivery accuracy and investigate plan robustness to different types of errors.